Particle size of a new endodontic cement compared to Root MTA and calcium hydroxide - Soheilipour, Elham; Kheirieh, Sanam; Madani, Majid; Akbarzadeh Baghban, Alireza; Asgary, Saeed (Iranian Endodontic Journal, 2009)
INTRODUCTION: Particle size and distribution can influence the properties of materials. This study analyzed and compared the particle size of Root MTA, calcium hydroxide (CH), and a new endodontic cement called calcium enriched material (CEM). MATERIALS AND METHODS: The particle size of each material was analyzed three times using 0.05 mg of test material with a particle size analyzer. The particle size distribution ranges, the cumulative percentage and the mean of particle sizes were calculated. One-way ANOVA, Tukey, and Chi-square tests were used for statistical analyses. RESULTS: Results demonstrated that the distribution of particles was dissimilar. Particle mean size in the three different materials was not significantly different. However, the cumulative percentage of CH and CEM cement particles size demonstrated significant difference (P<0.05). Among the various particle size distributions, the particle distribution in the size range of ≤30 μm showed significant difference between materials (P<0.05). Interestingly, the smallest range of particle size belonged to CEM cement. CONCLUSION: The high percentage of small particles found in CEM cement provides desirable properties such as effective seal, good setting time and film thickness in addition to favorable flow and adaptability.